Assessment of Student Satisfaction with Distance and Blended Learning - Renata Asali-van der Wal (National Research Mordova State University, 2023)
Introduction. Blended learning has gained prominence due to increased technological inclusion in the wake of post-Covid era. It comprises hybrid learning strategies where in-campus and online learning mediums are used. However, the students' satisfaction has become the most significant concern of the researchers in the context of the adoption of blended learning in the educational domain. The purpose of this article is to present the results of a study on the effectiveness of blended and distance learning in terms of student satisfaction. Materials and Methods. The study is quantitative in nature and purposively recruits 200 study participants who were either undergraduate students or diploma holders studying at a university. An online survey form was designed to collect data from the participants. The data collected was analyzed using Statistical Package of Social Sciences version 23.0. Descriptive Statistical Analysis using frequencies and percentages were used. Moreover, to find the association between students' satisfaction and blended and distance learning, ANOVA test was conducted. Results. The study shows that students' satisfaction had been greatly acknowledged as a significant factor in recognizing the courseʼs effectiveness, especially the blended learning course. In conclusion, this study provided positive feedback about hybrid learning methods and distance learning and their effect on studentsʼ satisfaction, leading to better learning and academic performance. Discussion and Conclusion. The findings of this study are significant for the teachers as they will be coordinating with the students and will be able to assist them in learning and management issues.